Characterization of Serum MicroRNAs Profile of PCOS and Identification of Novel Non-Invasive Biomarkers - Wei Long; Chun Zhao; Chenbo Ji; Hongjuan Ding; Yugui Cui; Xirong Guo; Rong Shen; Jiayin Liu (Cellular Physiology and Biochemistry, 2014)
Background: Polycystic ovary syndrome (PCOS), the most common endocrinopathy in women of reproductive age, is characterized by polycystic ovaries, chronic anovulation, hyperandrogenism and insulin resistance. Despite the high prevalence of hyperandrogenemia, a definitive endocrine marker for PCOS has so far not been identified. Circulating miRNAs have recently been shown to serve as diagnostic/prognostic biomarkers in patients with cancers. Our current study focused on the altered expression of serum miRNAs and their correlation with PCOS. Method and Results: We systematically used the TaqMan Low Density Array followed by individual quantitative reverse transcription polymerase chain reaction assays to identify and validate the expression of serum miRNAs of PCOS patients. The expression levels of three miRNAs (miR-222, miR-146a and miR-30c) were significantly increased in PCOS patients with respect to the controls in our discovery evaluation and followed validation. The area under the receiver operating characteristic (ROC) curve (AUC) is 0.799, 0.706, and 0.688, respectively. The combination of the three miRNAs using multiple logistic regression analysis showed a larger AUC (0.852) that was more efficient for the diagnosis of PCOS. In addition, logistic binary regression analyses show miR-222 is positively associated with serum insulin, while miR-146a is negatively associated with serum testosterone. Furthermore, bioinformatics analysis indicated that the predicted targets function of the three miRNAs mainly involved in the metastasis, cell cycle, apoptosis and endocrine. Conclusion: Serum miRNAs are differentially expressed between PCOS patients and controls. We identified and validated a class of three serum miRNAs that could act as novel non-invasive biomarkers for diagnosis of PCOS. These miRNAs may be involved in the pathogenesis of PCOS.